Transference iz angleščine v nemških sestavkih slovenskih učencev - Kač, Liljana (visokošolska dela, 2015)
The thesis deals with the influence of English as a first foreign language on learning and command of German as a second foreign language. The impact is defined as the occurrence of English transferences in compositions written in German by Slovenian students, since it has been known that in language learning there is a transfer from already acquired languages into a language being learnt. There is a great probability of crosslinguistic transfer in languages such as German and English since they are linguistically related, play an important social role, and are popular among students. The theoretical presentation of crosslinguistic influence, third language acquisition and comparison of linguistic features in both languages is followed by an outline of possible transferences by linguistic levels, taking into account the learner of Slovene as a first language. Furthermore, both learning and teaching of foreign languages are set in the social and individual context with a presentation of multilingualism as a European Union policy, learning and knowledge of foreign languages in the Slovenian education system, and the role of students' attitudes towards language learning and linguistic competence. In the empirical part of the thesis, the analysis of written compositions by learners of German in three consecutive years confirms our assumption about the expected maximum occurrence of English transferences at the lexical level (43.1 %); the occurrence is lower at the phonetic-orthographic level, (38.7 %) and the lowest at the morpho-syntactic level (18.2 %). The majority of transferences on the lexical level belong to the transference type of similar lexical items borrowing, most of which - by their origin - are from the common Germanic vocabulary. The most frequent types of transferences at the phonetic-orthographic level are as follows: the record of double consonants, the personal pronoun ich with a capital letter, and the dropping of the letter t in the personal verb form ist. At the morpho-syntactic level there are two dominant types of transference: formation of personal verb forms of modal verbs können, müssen and wollen and the formation of compound nouns. Furthermore, it has been found against our expectations - that the number of English transferences in German written compositions increased during the 3-year time period. The statistical correlation shows that a higher achievement in written composition is related to a lower number of transferences. The questionnaire filled in by the students as well as the statistical correlation between student responses and their achievements in learning the first and the second foreign languages show that students who learn German as a second foreign language are more successful if their attitude towards learning German and other languages is positive. On the basis of the scope and types of English transferences in written compositions, conclusions concerning third language acquisition and the importance of students' attitudes toward learning German some pedagogical recommendations for German classes parallel with English lessons were made. The recommendations are aimed at German teachers in order to plan and implement their German teaching in such a way as to exploit the potential of learner's knowledge of English, to raise the awareness of the importance of linking both languages and to improve the attitude towards learning German and languages in general. In this way, teaching German as a second foreign language can achieve a higher level, the progression may be steeper and contents more challenging so that students can achieve a higher level of knowledge in German and become better prepared for lifelong language learning.
Keywords: angleščina; crosslinguistic transfer; disertacije; dissertations; drugi tuji jezik; English; first foreign language; German; medjezikovni transfer; nemščina; prvi tuji jezik; second foreign language; third language acquisition; transference; transferences; večjezikovna didaktika